Utilization of Cervical Cancer Screening and its Associated Factors among Women in a Rural Municipality of Kapilvastu District, Nepal - Shrestha, Rubina; Bhusal, Chet Kant; Shrestha, Saneep; Chhetri, Pradip; Pokhrel, Gunjan; Shrestha, Neelam (Journal of Universal College of Medical Sciences, 2024)
INTRODUCTION Despite the fact that cervical cancer is a serious public health issue that affects women everywhere, very few women get screened for the disease. Early cervical cancer screening has a clear effect on lowering cervical cancer related morbidity and mortality. Therefore, this study aimed to assess the use of cervical cancer screening and the factors that are associated with it. MATERIAL AND METHODS Community based cross-sectional study was employed from May to October 2023 in a rural municipality of Kapilvastu district, Nepal. Total 240 married women were interviewed. A logistic regression model was used and an adjusted odds ratio calculated with a 95% conﬁdence interval at p-value <0.05 to determine the factors associated with cervical cancer screening utilization. RESULTS The study revealed that 76 (31.7%) of women have been screened for cervical cancer. Respondent’s education [AOR: 0.353, 95%CI( 0.172-0.724)], women engaged in agriculture [AOR: 0.168, 95%CI (0.041-0.699)], housewife’s [AOR: 0.141, 95%CI (0.039-0.518)], age of marriage [AOR: 2.230, 95%CI (1.043-4.766)], duration of family planning used [AOR: 0.208, 95%CI (0.073-0.589)], history of sexually transmitted infection [AOR: 2.630,95%CI (1.033-6.699)], level of knowledge [AOR:0.320,95%CI (0.146-0.702] and attitude towards screening [AOR: 0.252,95%CI (0.108-0.589)] were signiﬁcant factors for utilization of cervical cancer screening. CONCLUSION According to the ﬁndings, less than one third of respondents had undergone cervical cancer screening. Furthermore, it provides information on a number of variables related to the use of cervical cancer screening. As a result, the local government should focus on the identiﬁed factors for implementing programs to enhance cervical cancer screening.